Esophagogastric junction distensibility on functional lumen imaging probe topography predicts treatment response in achalasia – anatomy matters! - Jain, Anand S (Am J Gastroenterol, 2019)
BACKGROUND AND AIMS: To compare the utility of the distensibility index (DI) on functional lumen imaging probe (FLIP) topography to other esophagogastric junction (EGJ) metrics in assessing treatment response in achalasia in the context of esophageal anatomy. METHODS: We prospectively evaluated 79 patients (ages 17-81, 47% female) with achalasia during follow-up after pneumatic dilation, heller myotomy, or per-oral endoscopic myotomy with timed barium esophagram (TBE), high resolution manometry (HRIM) and FLIP. Anatomic deformities were identified based on consensus expert opinion. Patients were classified based on anatomy and EGJ opening to determine association with radiographic outcome and Eckardt score (ES). RESULTS: Twenty-seven patients (34.1%) had an anatomic deformity – 10 pseudodiverticula at myotomy, 7 epiphrenic diverticula, 5 sigmoid, and 5 sinktrap. A 5-min column area of >5 cm(2) was best associated with an ES>3, with a sensitivity of 84% (p=.0013). Area-under-the curve for EGJ metrics in association with retention were as follows: DI-.90, MxEGJD-.76, IRP-.64, EGJP-.53. Only FLIP metrics were associated with retention given normal anatomy (DI 2.4 vs 5.2 mm(2)/mmHg, and MxEGJD 13.1 vs 16.6 mm in patients with vs without retention, p values <.0001 and .002). Using a DI cutoff of <2.8 as abnormal, 40/45 patients with retention (p=.0001) and 23/25 patients with an ES>3 (p=.02) had a combination of a low DI and/or anatomic deformity. With normal anatomy, 21/22 patients with retention had a low or borderline low DI. CONCLUSIONS: The FLIP DI is most useful metric for assessing the effect of achalasia treatment on EGJ opening. However, abnormal anatomy is an important mediator of outcome and treatment success will be modulated by anatomic defects that impede bolus emptying.